Stability of Chlorine Termination on Ge(100) and Ge(111) Surfaces - Siti Kudnie, Sahari; Muhammad, Kashif; Marini, Sawawi; Nik Amni Fathi, Nik Zaini Fathi; Azrul Azlan, Hamzah; Burhanuddin, Yeop Majlis; Norsuzailina, Mohamed Sutan; Rohana, Sapawi; Kuryati, Kipli; Marini, Sawawi; Nurul Atiqah, Abdul Halim; Nazreen, Junaidi; et al. (EDP Sciences, 2017)
The different cleaning solution; HCl and HF solution are used to remove the suboxide and oxide component on Ge surface. The HCl cleaning results chlorine (Cl) termination on Ge surface whereas no Fluorine (F) termination was observed just after HF cleaning. The growth of Ge oxide is studied after treated with HCl cleaning on two surface orientations; (100) and (111), respectively in dry oxygen ambient and cleanroom air by spectroscopic ellipsometry (SE) and x-ray photoelectron spectroscopy (XPS). A clear step and terrace trend was observed for the oxidation growth of Ge (100) and Ge (111) in dry oxygen ambient compared to in clean room air. This trend shows the difference in surface reaction of Ge oxidation as humidity varies. The stability of chlorine termination of Ge (111) than Ge (100) explains the slower growth of oxidation in dry oxygen ambient.